Modulation of relativistic electron beam characteristics by 3D-printed periodic structures; Radiation from Relativistic Electrons in Periodic Structures, RREPS-25 - Miloichikova I. A. Irina Alekseevna; Bulavskaya A. A. Angelina Aleksandrovna; Polomoshnova D. A. Darjya Anatoljevna; Stuchebrov S. G. Sergey Gennadevich (2025, 2025)
Title screen